Long‐term organic carbon sequestration in tidal marsh sediments is dominated by old‐aged allochthonous inputs in a macrotidal estuary. (2nd March 2018) - Van de Broek, Marijn; Vandendriessche, Caroline; Poppelmonde, Dries; Merckx, Roel; Temmerman, Stijn; Govers, Gerard
Abstract: Tidal marshes are vegetated coastal ecosystems that are often considered as hotspots of atmospheric CO2 sequestration. Although large amounts of organic carbon (OC) are indeed being deposited on tidal marshes, there is no direct link between high OC deposition rates and high OC sequestration rates due to two main reasons. First, the deposited OC may become rapidly decomposed once it is buried and, second, a significant part of preserved OC may be allochthonous OC that has been sequestered elsewhere. In this study we aimed to identify the mechanisms controlling long‐term OC sequestration in tidal marsh sediments along an estuarine salinity gradient (Scheldt estuary, Belgium and the Netherlands). Analyses of deposited sediments have shown that OC deposited during tidal inundations is up to millennia old. This allochthonous OC is the main component of OC that is effectively preserved in these sediments, as indicated by the low radiocarbon content of buried OC. Furthermore, OC fractionation showed that autochthonous OC is decomposed on a decadal timescale in saltmarsh sediments, while in freshwater marsh sediments locally produced biomass is more efficiently preserved after burial. Our results show that long‐term OC sequestration is decoupled from local biomass production in the studied tidal marsh sediments. This implies that OC sequestration rates are greatly overestimated when they are calculated based on short‐term OC deposition rates, which are controlled by labile autochthonous OC inputs. Moreover, as allochthonous OC is not sequestered in‐situ, it does not contribute to active atmospheric CO2 sequestration in these ecosystems. A correct assessment of the contribution of allochthonous OC to the total sedimentary OC stock in tidal marsh sediments as well as a correct understanding of the long‐term fate of locally produced OC are both necessary to avoid overestimations of the rate of in‐situ atmospheric CO2 sequestration in tidal marsh sediments. Abstract : Tidal marshes store large amounts of organic carbon in their sediments and have been identified as hotspots of blue carbon sequestration. Our results show, however, that a substantial portion of organic carbon in the studied tidal marsh sediments is very old, allochthonous carbon which was deposited at the tidal marsh platform during inundation events. This carbon did consequentially not contribute to atmospheric CO2 sequestration in these ecosystems. Therefore, the results of this study show the importance of accounting for allochthonous carbon deposition on tidal marshes in order not to overestimate calculated rates of atmospheric CO2 sequestration in these ecosystems.